Understanding the Key Role of Atmospheric Processing in Determining the Oxidative Potential of Airborne Engineered Nanoparticles - Liu, Qifan; Shahpoury, Pourya; Liggio, John; Harner, Tom; Li, Kun; Lee, Patrick; Li, Shao-Meng (ENVIRONMENTAL SCIENCE & TECHNOLOGY LETTERS, 2020)
Inhalation of airborne engineered nanoparticles (ENPs) is an important pathway for population exposure. While there have been numerous studies of the health impacts of pristine ENPs, the impacts of atmospherically transformed ENPs are largely unknown, despite the certainty that atmospheric processing of ENPs will occur. Here, the oxidative potential (OP) of TiO2, CeO2, and SiO2 nanoparticles which had been coated with atmospheric secondary organic material (SOM) from the OH or O-3 oxidation of alpha-pinene and toluene was investigated. The results indicated that coating of these ENPs with SOM formed at low photochemical ages reduced the OP of redox-active ENPs (TiO2 and CeO2) and increased the OP of redox-inert ENP (SiO2). However, at a given SOM coating thickness, the overall OP of the particles increased by up to 93% with an increased level of photooxidation, regardless of ENP type. The OP suppression and enhancement observed here were attributed to a physical hindrance of ENP-antioxidant interactions by the SOM and an enhanced peroxide content in SOM (brought about by an increased level of photooxidation), respectively. These results imply that the health risk associated with airborne ENPs is strongly related to their time history during their residence time in the atmosphere, and thus, accounting for the impacts of atmospheric processing should be considered critical for making accurate risk assessments of airborne ENPs and for formulating efficient policies with respect to the control of emerging nanotechnologies.